Subsurface Analysis of Sibayak Mountain Karo Regency Using Geomagnetic Method with 2D and 3D Modeling - Putri, Nadinda Dwi; Lubis, Lailatul Husna; Sirait, Ratni (Lambung Mangkurat University Press, 2024)
Mount Sibayak is a quaternary volcano located in the Berastagi area, located in the northern part of the island of Sumatra, approximately 25 km north of Lake Toba. However, the rocks produced are very different from rocks of the same age in Sumatra, Java, and the Toba Tufa. To dig up information about the subsurface structure of the Mount Sibayak area, Karo Regency, use Geophysics. This research uses the geomagnetic method to interpret subsurface layers and rock types based on the intensity of the magnetic field measured at the surface. Measurements were carried out using the PPM GMS 19T (Proton Procession Magnometer) tool by taking data from 51 measurement points with a range of ±10 meters at each measuring point. Data processing begins with IGRF correction, separation of regional and residual anomalies using a bandpass filter, reduction to the poles, and data interpretation. Data modeling uses Oasis Montaj for 2D modeling and ZondGM3D for 3D modeling. The subsurface lithology of Mount Sibayak, Karo Regency, can be seen in the subsurface of the research area. There are two types of rock, namely clay rock as a capping rock, which is altered due to hydrothermal flows with susceptibility contrast values ranging from berkisar (-10 x 10-3) – (-2 x 10-3) SI and rock andesite intrusions containing hydrothermal fluids with susceptibility contrast values ranging from (35 x 10-3) – (50 x 10-3) SI